Author Correction: Neuroimmune disorders of the central nervous system in children in the molecular era. Issue 12 (December 2018) - Wells, Elizabeth; Hacohen, Yael; Waldman, Amy; Tillema, Jan; Soldatos, Ariane; Ances, Beau; Benseler, Susanne; Bielekova, Bibi; Dale, Russel; Dalmau, Josep; Gaillard, William; Gorman, Mark; et al.
In the original version of this Review published online and in print, the contribution of attendees of the International Neuroimmune Meeting to the content of the Review was not acknowledged. The author list has been corrected in the PDF and HTML versions of this article to acknowledge that the Review was written on behalf of attendees of the International Neuroimmune Meeting, and the names of the attendees have been added to the HTML version.